Myocarditis Mimicking an Acute Coronary Syndrome: A Case Related to Salmonella enteritis - B. Rossetti; G. Nguisseu; A. Buracci; L. Migliorini; G. Zanelli (Gastroenterology Research and Practice)
Infective myocarditis is most commonly due to a viral infection; occasionally it has been related to bacteria. Gastrointestinal infections associated with myocarditis have only rarely been described in young people, and the pathogenesis is unclear. We report a case of myocarditis mimicking an acute coronary syndrome (ACS) in a patient hospitalized for fever and diarrhoea. Salmonella enteritidis was isolated from stool, and no other pathogens were found. The coronary angiography was normal, and there were not other coronary artery risk factors, other than hypertension. The patient was treated with ciprofloxacin, acetylsalicylate acid, and ramipril with rapid clinical improvement and normalization of cardiac abnormalities. Final diagnosis of Salmonella enteritis and related myocarditis was made based on clinical, laboratory, ECG and echocardiographical findings.